Prevalence of Skin Findings among Libyan Diabetic Patients. - A. Albarghathi , Ghada; A. Najm, Antisar; B. Trapolsi , Aisha; J. Awad , Shadia (Benghazi University Medical Journal, 2025)
Abstract Background: Diabetes mellitus (DM) is the most common endocrine disorder. Almost one-third of diabetic patients are affected by cutaneous manifestations during their disease. Cutaneous manifestations of diabetes are caused by either diabetes-induced metabolic changes in the skin or by associated complications like vasculopathy and neuropathy. Objectives: To estimate the prevalence of skin diseases among patients with diabetes mellitus. Method: One hundred eighty known adult diabetic patients of either sex attending the outpatient clinic of the diabetic center (Diabetic Center / Benghazi / Libya) for treatment and follow-up of diabetes were randomly selected for the study. Detailed case history of each patient with special attention to cutaneous lesions were taken. A dermatologist performed a detailed dermatological examination. Results: In this study, most diabetes patients ranged from 41 to 60 years for females, while for males, they were over 60 years. The majority of patients in the current study were females. The most common dermatosis associated with DM was acanthosis nigricans; seen in (69.4%) of patients, skin tag was the second most common dermatosis, accounting for (56.7%) of patients, xerosis was seen in (54.4%), pruritus seen in (37.2%), fungal skin infections found in (25.6%). Diabetic dermopathy was seen in (17.7%), and prayer signs were found in (10.6%). Fifteen (8.3%) diabetic patients had nail changes, and eight (4.4%) diabetic patients had foot ulcers. Diabetic bullae were found in (2.2%); as well as viral infections were seen in (2.2%). Two (1.1%) diabetic patients have bacterial infections. Conclusion: The prevalence of certain dermatoses was increased among diabetic patients. So, diabetic patients are considered to be at risk of developing certain skin diseases.